A Brief Study of German Sinology Origins and the Dissemination of Daoism - Terol Rojo, Gabriel (Sinología hispánica. China Studies Review, 2018)
The dissemination of Daoism in the West is a process that, although it begins late and slow, will lead to the great interest that this way of thinking has finally awakened, not only in the academic field, but also in some popular media. In order to clarify the history of the Western study of Chinese doctrine, the present article reviews the contribution of what we call the German sinology until the mid-twentieth century to focus the contribution of the Germanic works. With the recognition that the first works in German language on the Daoism are due to the Austrian sinologist and Japanese scholar August Pfitzmaier, we review the history of sinology in Germany highlighting authors and summarizing their biographies, works and Daoist contributions: Andreas Müller, for his Clavis Sinica; Christian Mentzel, engaged in linguistic works; Gottlieb Bayer, for his Museum Sinicum in quo Sinicæ linguæ et litteraturæ ratio explicatur; Julius Klaproth, the first German to excel in modern sinology and Georg von der Gabelentz, for his pioneering Beiträge zur chinesischen Grammatik, die Sprache des Chuang-Tsi. From the eighteenth century and with the beginnings of Sino-German relations: Ernst Faber, the undisputed Richard Wilhelm and Otto Franke. In the second half of the twentieth century, there was a resurgence of sinological studies throughout Germany, where the war had stopped these activities and had forced numerous renowned specialists such as Ernest Julius Walter Simon and Erich Haenisch to escape. July 2017 October 2017 Received: Accepted: The dissemination of Daoism in the West is a process that, although it begins late and slow, will lead to the great interest that this way of thinking has finally awakened, not only in the academic field, but also in some popular media. In order to clarify the history of the Western study of Chinese doctrine, the present article reviews the contribution of what we call the 1 Esta investigación formó parte del trabajo doctoral realizado por el autor dentro del programa oficial de doctorado de la Facultad de Filosofía de la Universidad de Valencia (España), "Razón, Lenguaje e Historia" (627 165F).